The Effects of Anesthesia on Adult Hippocampal Neurogenesis - Kim, Jenny L.; Bulthuis, Nicholas E.; Cameron, Heather A. (Frontiers in Neuroscience, 2020)
In animal studies, prolonged sedation with general anesthetics has resulted in cognitive impairments that can last for days to weeks after exposure. One mechanism by which anesthesia may impair cognition is by decreasing adult hippocampal neurogenesis. Several studies have seen a reduction in cell survival after anesthesia in rodents with most studies focusing on two particularly vulnerable age windows: the neonatal period and old age. However, the extent to which sedation affects neurogenesis in young adults remains unclear. Adult neurogenesis in the dentate gyrus (DG) was analyzed in male and female rats 24 hours after a 4-hour period of sedation with isoflurane, propofol, midazolam, or dexmedetomidine. Three different cell populations were quantified: cells that were one week or one month old, labeled with the permanent birthdate markers EdU or BrdU, respectively, and precursor cells, identified by their expression of the endogenous dividing cell marker proliferating cell nuclear antigen (PCNA) at the time of sacrifice. Midazolam and dexmedetomidine reduced cell proliferation in the adult DG in both sexes but had no effect on postmitotic cells. Propofol reduced the number of relatively mature, 28-day old neurons specifically in female rats and had no effects on younger cells. Isoflurane had no detectable effects on any of the cell populations examined. These findings show no general effect of sedation on adult-born neurons but demonstrate that certain sedatives do have drug-specific and sex-specific effects. The impacts observed on different cell populations predict that any cognitive effects of these sedatives would likely occur at different times, with propofol producing a rapid but short-lived impairment and midazolam and dexmedetomidine altering cognition after a several week delay. Taken together, these studies lend support to the hypothesis that decreased neurogenesis in the young adult DG may mediate the effects of sedation on cognitive function.